Late onset 'en coup de sabre' following trauma: Rare presentation of a rare disease - Tasleem Arif; Imran Majid; Mir Laieq Ishtiyaq Haji (Our Dermatology Online, 2015)
En coup de sabre (linear scleroderma of face) is a rare type of morphea (localized scleroderma) involving frontoparietal area of the forehead and scalp. Many triggering factors have been implicated in the development of morphea like trauma, immobilization, bacille Calmette-Guérin (BCG) vaccination, injections of vitamin K, mechanical compression from clothing, etc. Linear scleroderma primarily affects the pediatric population, with 67% of patients diagnosed before 18 years of age. In this article, we describe a case of 26 year old female who presented with a three months history of brownish indurated plaque of skin on the frontal and forehead regions of the head. The patient gave a history of trauma at the same site six years back. The diagnosis of morphea was made clinically supported by histopathological features of the skin biopsy. Her neurological examination was normal. ANA was negative. Brain MRI didn't reveal any abnormality. She was treated with topical tacrolimus 0.1% ointment. The late onset en coup de sabre is a rare presentation and hence reported.